Tinjauan Teologis Panggilan Debata Terhadap Iman Kristen Dalam Masyarakat Batak Toba - Rajiman Andrianus Sirait; Timotius Sukarna (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This article will discuss the role of "debata" theology of calling within the context of Christian faith in Batak society, Indonesia. "Debata" theology of calling refers to the teachings and customary traditions of the Batak people that regulate the duties, responsibilities, and obligations of individuals within the community. This article will analyze how "debata" theology of calling influences the practices and perceptions of the Christian faith among the Batak community. The literature sources utilized in this article include research, books, and papers related to Christian theology and Batak culture.